Working in archaeology in a changing world: Australian archaeology at the beginning of the COVID-19 pandemic. Issue 3 (2nd September 2021) - Mate, Geraldine; Ulm, Sean
Abstract: The COVID-19 pandemic is transforming the global labour market, including the Australian archaeological profession. This, the fourth in a series of comprehensive surveys of Australian professional archaeologists undertaken in early 2020, provides longitudinal data on trends in the state of the archaeological profession in Australia. Findings include the early impacts of COVID-19. Headline results show a young (average age 42 years), well-qualified (92% holding an Honours degree or higher), well-renumerated (average salary AUD102, 430) workforce focused on Indigenous archaeology (65%), working in the private sector (60%), and predominantly based on the eastern seaboard (78%). Longitudinal data show an expanding archaeological industry in Victoria and a softening of demand in all other states and territories, particularly Western Australia. Sex and age data show a profession dominated by females (58%) with increasing numbers of young females in the career pipeline (average age of males 46 years and females 40 years). Indigenous participation rates in professional archaeology remain low (1.9%). The impact of COVID-19 had a considerable effect on confidence in stability or growth in the coming year, with a slump of 15% across the profession after the declaration of the pandemic. But confidence remained positive at 58% overall. Data show slowing wages growth (6.5% over 5 years compared to the national average of 11.4%) and a continuing profound gender pay gap of 18.8%, or on average males taking home $17, 800 more than females.